Efficient astronomical data condensation using approximate nearest neighbors - Łukasik, Szymon; Lalik, Konrad; Sarna, Piotr; Kowalski, Piotr A.; Charytanowicz, Małgorzata; Kulczycki, Piotr (Zielona Góra: Uniwersytet Zielonogórski)
Extracting useful information from astronomical observations represents one of the most challenging tasks of data exploration. This is largely due to the volume of the data acquired using advanced observational tools. While other challenges typical for the class of big data problems (like data variety) are also present, the size of datasets represents the most significant obstacle in visualization and subsequent analysis.
Keywords: big data; astronomy; data reduction; nearest neighbor search; kd-trees